Hemopatch Application for Ventricular Wall Laceration in Redo Cardiac Surgical Procedures - Sandrio, Stany; Purbojo, Ariawan; Cesnjevar, Robert; Rueffer, Andre (Annals of Thoracic Surgery, 2016)
As survival among patients with complex congenital heart disease continues to improve, long-term survivors frequently require redo surgical procedures, with potentially escalating technical difficulty and bleeding risk. This report describes our experience with a new hemostatic pad, Hemopatch (Baxter Deutschland GmbH, Unterschleissheim, Germany) in redo cardiac surgery.
EVALuna2:25811